Documentation of the nursing process in public health institutions - Azevedo, Oswalcir Almeida de; Guedes, Érika de Souza; Araújo, Sandra Alves Neves; Maia, Magda Maria; Cruz, Diná de Almeida Lopes Monteiro da (Revista da Escola de Enfermagem da USP, 2019)
Objective To identify the prevalence of nursing process documentation in hospitals and outpatient clinics administered by the São Paulo State Department of Health. Method A descriptive study conducted through interviews with nurses responsible for 416 sectors of 40 institutions on the documentation of four phases of the Nursing Process (data collection, diagnosis, prescription and evaluation) and nursing annotations. Results Of the 416 sectors studied, 89.9% documented at least one phase; 56.0% documented the four phases; 4.3% only documented nursing annotations; 5.8% did not document any phase, nor did the nursing notes. The types of sectors which were less documented were: ambulatory, diagnostic support, surgical center and obstetric center; while the ones which were most documented included: intensive care units, emergency rooms and hospitalization units. The data collection and diagnosis were the least documented phases, both in 78.8% of the sectors. Conclusion Most of the studied sectors document the Nursing Process and do nursing annotations, but there are sectors where documentation does not meet formal requirements. The viability of documentation of all the Nursing Process phases in certain types of sectors needs to be better studied.